PERAN IKLIM KERJA-KELUARGA DAN BEBAN BERLEBIH KERJA-KELUARGA DALAM MEMPREDIKSI KONFLIK KERJA-KELUARGA PADA KARYAWAN BANK PERKREDITAN RAKYAT (BPR) - Rusmalia Dewi; Gusti Y. Asih; M. M. Shinta Pratiwi (Jurnal Psikologi, 2023)
Work and family problems in working adults are very complex during this pandemic, especially for those who are married and have children. Many role demands must be met from the work and family domains or are called work-family conflicts. The consequences of ongoing work-family conflict can be detrimental to individual health physically and psychologically, so prevention efforts are made by examining the role of the antecedent variables, namely work-family climate and work-family overload on work-family conflict. This study aims to examine the role of work-family climate and work-family overload on work-family conflict. The method used is quantitative. The research subjects were BPR Central Java and DIY employees. Statistical analysis with multiple regression tests. The sampling method uses simple random sampling. The results showed that there was a significant influence between work-family climate, work-family overload and work-family conflict on BPR employees (Rsquare = 0.505 p < 0.001). Work-family overload greatly influences work-family conflict ( r= 0.69) and work-family climate contributes (r = -0.22) to reducing work-family conflict among employees. These two variables contribute 50.5% to work-family conflict among BPR employees in Central Java and DIY. The ability of BPR employees to manage work-family conflict can prevent the consequences of work-family conflict, such as protecting their physical and psychological health so that they are able to improve their performance and quality of life in the post-pandemic period.